Best Practices in Processing and Storage for Hematopoietic Cell Transplantation (Advances and Controversies in Hematopoietic Transplantation and Cell Therapy,, 2018)
This concise book examines clinically relevant issues relating to the ways in which bone marrow, cord blood and apheresis products, are processed and stored for the purpose of Hematopoietic Cell Transplantation and Cell Therapy. The twin aims are to offer up-to-date content covering a wide spectrum of topics and controversies and to provide practitioners in the field of transplant and cell therapy with practical, immediately applicable information from the internationally experts in the field. Each chapter focuses on a particular subject, and numerous working tables, algorithms, and figures are included. Whenever appropriate, the reader's attention is drawn to the availability of potentially high-impact clinical trials and expert practices. The authors are all experts who have been carefully selected for their knowledge of the topics that they address. The book will appeal to clinical and laboratory personnels, residents, fellows, and faculty members responsible for the care of hematopoietic cell transplant products and patients. Its format ensures that it will also serve as a robust, engaging tool to aid vital activities in every hematology and oncology trainee's daily work.